Uniqueness Theorems on Entire Functions and Their Difference Operators or Shifts - Baoqin Chen; Zongxuan Chen; Sheng Li (Abstract and Applied Analysis)
We study the uniqueness problems on entire functions and their difference operators or shifts. Our main result is a difference analogue of a result of Jank-Mues-Volkmann, which is concerned with the uniqueness of the entire function sharing one finite value with its derivatives. Two relative results are proved, and examples are provided for our results.